MODERN APPROACHES TO TEACHING AND ASSESSING ENGLISH LANGUAGE SKILLS BASED ON CEFR STANDARDS - Abduraximov Murodbek Baxtiyor oʻgʻli; Xo'shboqov Sarvar Bahrom o'gli; Husanov Abdurahmon Juma oʻgʻli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract The Common European Framework of Reference for Languages (CEFR) has become one of the most influential instruments guiding English language pedagogy and assessment across educational systems worldwide. This article investigates contemporary instructional and evaluative approaches that align with CEFR descriptors, focusing on how action-oriented tasks, communicative methodology, and authentic assessment enhance learner performance across the four core language skills. Drawing on document analysis, comparative research on international examinations, and expert-based synthesis, the study demonstrates that CEFR-informed teaching not only ensures transparency in learning outcomes but also supports more reliable and equitable assessment procedures. The findings reaffirm that integrating CEFR standards with task-based learning, formative assessment, and technology-assisted feedback significantly improves language proficiency development, learner autonomy, and instructional coherence.